Effects of Speed Sintering on Multilayered Monolithic Zirconia - Mehmet Coskun; Fatih Sarı (Cumhuriyet University, 2019)
Objective:In dentistry, different products are being developed in order to shorten the chairside but the interactions between these materials needs further investigations. This study aims to investigate the two different short time sintering protocols on monolithic multilayered zirconia's surface roughness (SR), translucency parameter (TP), and contrast ratio (CR).  Material and Methods:Twenty monolithic multilayer zirconia specimens were prepared with the dimension 10x10x1 mm and divided into two sintering groups (speed sintering group 30 min at 1510 0C, high speed sintering group 10 min 1580 0C) and SEM analyzed were performed. Surface roughness tests were performed by using profilometer and optical measurements were performed by using spectrophotometer. The data was statistically analyzed by using Wilcoxen test at the 0.05 probability level.Results:SR values and CR did not show any significant difference at any layer of any group. In all parts of monolithic multilayered zirconia, the difference of TP between sintering groups were statistically significant (P<.05). Conclusion: High speed sintering parameters has promising effects on monolithic multilayered zirconia with combined acceptable optical properties. Because of their different content, different layers show different reactions in terms of contrast ratio and translucency parameters and these changes should be taken into account in treatment planning.